Safety and efficacy of the FRED Jr Flow Re-Direction Endoluminal Device for Intracranial aneurysms: retrospective multicenter experience with emphasis on midterm results - Jesser, Jessica; Alberalar, Nilüfer D.; Kizilkilic, Osman; Saatci, Isil; Baltacioglu, Feyyaz; Özlük, Enes; Killer-Oberpfalzer, Monika; Vollherbst, Dominik; Islak, Civan; Cekirge, Saruhan H.; Bendszus, Martin; Möhlenbruch, Markus Alfred; et al. (Frontiers in neurology, 2021)
Background and Purpose: Flow diversion is increasingly used as an endovascular treatment for intracranial aneurysms. In this retrospective multicenter study, we analyzed the safety and efficacy of the treatment of intracranial, unruptured, or previously treated but recanalized aneurysms using Flow Re-Direction Endoluminal Device (FRED) Jr with emphasis on midterm results.Materials and Methods: Clinical and radiological records of 150 patients harboring 159 aneurysms treated with FRED Jr at six centers between October 2014 and February 2020 were reviewed and consecutively included. Clinical outcome was measured by using the modified Rankin Scale (mRS). Anatomical results were assessed according to the O'Kelly-Marotta (OKM) scale and the Cekirge-Saatci Classification (CSC) scale.Results: The overall complication rate was 24/159 (16%). Thrombotic-ischemic events occurred in 18/159 treatments (11%). These resulted in long-term neurological sequelae in two patients (1%) with worsening from pre-treatment mRS 0-2 and mRS 4 after treatment. Complete or near-complete occlusion of the treated aneurysm according to the OKM scale was reached in 54% (85/158) at 6-month, in 68% (90/133) at 1-year, and in 83% (77/93) at 2-year follow-up, respectively. The rates of narrowing or occlusion of a vessel branch originating from the treated aneurysm according to the CSC scale were 11% (12/108) at 6-month, 20% (17/87) at 1-year, and 23% (13/57) at 2-year follow-up, respectively, with all cases being asymptomatic.Conclusions: In this retrospective multicenter study, FRED Jr was safe and effective in the midterm occlusion of cerebral aneurysms. Most importantly, it was associated with a high rate of good clinical outcome.
Gesehen am 24.12.2021